Role of SARM1 and DR6 in retinal ganglion cell axonal and somal degeneration following axonal injury - Fernandes, Kimberly A. (Exp Eye Res, 2018)
Optic neuropathies such as glaucoma are characterized by the degeneration of retinal ganglion cells (RGCs) and the irreversible loss of vision. In these diseases, focal axon injury triggers a propagating axon degeneration and, eventually, cell death. Previous work by us and others identified dual leucine zipper kinase (DLK) and JUN N-terminal kinase (JNK) as key mediators of somal cell death signaling in RGCs following axonal injury. Moreover, others have shown that activation of the DLK/JNK pathway contributes to distal axonal degeneration in some neuronal subtypes and that this activation is dependent on the adaptor protein, sterile alpha and TIR motif containing 1 (SARM1). Given that SARM1 acts upstream of DLK/JNK signaling in axon degeneration, we tested whether SARM1 plays a similar role in RGC somal apoptosis in response to optic nerve injury. Using the mouse optic nerve crush (ONC) model, our results show that SARM1 is critical for RGC axonal degeneration and that axons rescued by SARM1 deficiency are electrophysiologically active. Genetic deletion of SARM1 did not, however, prevent DLK/JNK pathway activation in RGC somas nor did it prevent or delay RGC cell death. These results highlight the importance of SARM1 in RGC axon degeneration and suggest that somal activation of the DLK/JNK pathway is activated by an as-yet-unidentified SARM1-independent signal.